2015
DOI: 10.1590/01000683rbcs20150030
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Soil Physical Quality in Northern China Based on S-theory

Abstract: Quantitative assessment of soil physical quality is of great importance for eco-environmental pollution and soil quality studies. in this paper, based on the S-theory, data from 16 collection sites in the haihe river Basin in northern China were used, and the effects of soil particle size distribution and bulk density on three important indices of the S-theory were investigated on a regional scale. the relationships between unsaturated hydraulic conductivity K i at the inflection point and S values (S/h i ) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These authors emphasized the sensitivity of this index to soil structural change, even though it is very small, and concluded that the S-index is a good tool for monitoring soil physical quality. Yang et al (2015) also showed a negative linear correlation between S-index and SD (1.35 to 1.55 Mg m -3 ) in soil samples (150 to 350 g kg -1 clay) collected in northern China, but with low R 2 (0.02), which may indicate a lack of correlation between these parameters; and the SD was considered less important than the clay content.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…These authors emphasized the sensitivity of this index to soil structural change, even though it is very small, and concluded that the S-index is a good tool for monitoring soil physical quality. Yang et al (2015) also showed a negative linear correlation between S-index and SD (1.35 to 1.55 Mg m -3 ) in soil samples (150 to 350 g kg -1 clay) collected in northern China, but with low R 2 (0.02), which may indicate a lack of correlation between these parameters; and the SD was considered less important than the clay content.…”
Section: Resultsmentioning
confidence: 91%
“…Even in view of the uncertain efficiency of the S-index, Yang et al (2015) considered it as an indicator of soil physical quality. They found a mean S-index of 0.77 in the northern China basin and classified it as indicative of good soil quality.…”
Section: S-index Ofmentioning
confidence: 99%
“…Obviously, more analysis is required in future studies. We should have made this clear in the discussion in our study (Yang et al, 2015).…”
mentioning
confidence: 85%
“…We are grateful to De Jong van Lier for raising queries about our study (Yang et al, 2015) which merits some clarification, and we would like to reply to his comments.…”
mentioning
confidence: 99%
See 1 more Smart Citation